SOCIO-PERSONAL FACTORS AS PREDICTORS OF PSYCHOLOGICAL ADJUSTMENT OF EXCEPTIONAL STUDENTS IN IBADAN, NIGERIA - Ikani, Egaga, Patrick; Akintunde, Dada Oluseyi; Olujide, Fagbemi Olusegun (European Scientific Journal, ESJ, 2015)
This study is an investigation into the influence of some social and personal factors on psychological adjustment of high ability students in Ibadan, Nigeria. Expo-facto design of correlation type was used for the study. A sample of 160 high ability students in selected schools in Ibadan participated in the study. Four research questions guided the study. Five instruments were used for this study namely Peer Pressure and Popularity Scale, Parenting Style Inventory, and Self-Esteem Scale, Psychological Adjustment Scale, and Self-Concept Scale. There were correlations between parenting styles, peer acceptance, self-concept, and psychological adjustment. The four independent variables made significant contributions to psychological adjustment of the participants with parenting styles (b= 1.45, 7.356; p<0.05), peer acceptance (b= -1.67, 6.451, p<0.05) and self-concept (b= 1.23, 6.872, p<0.05) while parenting styles was found to be the most potent predictor of psychological adjustment of the participants (b= 1.45, 7.356; p<0.05). When the four variables combined they yielded very strong effect on psychological adjustment i.e. an F-ratio value of 12.207 at 0.05 level i.e. (F (4, 155) = 12.207; p<0.05). Recommendations made include the need for parents to imbibe parenting styles which will encourage their children to adjust well to emotional and psychological issues.